PENGARUH KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PERGURUAN TINGGI LA TANSA MASHIRO RANGKASBITUNG - Zakiyya Tunnufus; Iman Iman (Universitas La Tansa Mashiro, 2018)
The method used in this research quantitative method In this study the population used is the employment and social workforce in the regency lebak that is 32 respondents using Saturation sampling technique Data analysis technique used is validity test, reliability test, normality test, simple product regression coefficient, coefficient of determination and hypothesis test that is processed using computer software that is SPSS (statistic program for social science) version 20 From the test results that have been done shows that there is a significant influence between Transformational Leadership on Employee Performance in the Office of Labor and Social in Lebak District